Evaluating the nexus between health expenditure and health outcomes with consideration for income characteristics in SSA countries - Ebere Ume Kalu; Chuck Augustine Arize; Felicia Osondu Okwueze; Ndubuisi Udemezue (Future Business Journal)
Abstract This paper revisits the interaction between health expenditure and health outcomes and government effectiveness with consideration for the income classification of the investigated countries. It is an inquiry into the degree to which income status of countries can influence the health expenditure and health outcome nexus in the SSA countries. The data for the study were drawn from sub-Saharan African Countries (SSA) covering the period 1960–2020. The study follows a country-specific comparative approach using the autoregressive distributed lag model (ARDL) as the major estimation technique. It was discovered that poor health outcomes are not just due to inadequate budgetary allocations to the sector, but it is also symptomatic of the inefficiency associated to management of public resources in SSA countries. The study further found cointegrating relationship and strong adjustment of health outcomes to the shocks and dynamics of not just health expenditure but also government effectiveness. In the income classification dimensions, it was found out that the health expenditure and outcome nexus in high- and middle-income countries of SSA tend to be higher as income status gave vent to higher budgetary allocation. It is therefore that strong institutions, improved budgetary allocation and support for the low-income countries be made to increase the beneficial impact of public health spendings.